The New Global Superpower Geo- Startegic And Geo-Economics Rivalry In The Red Sea And Its Implication On Peace And Security In The Horn Of Africa - Surafel Getahun (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2023)
This article analyses the recent year’s port and military base competitions and rivalries between international, regional and local powers in the Red Sea and its implication on peace and security of Horn of Africa the region. The super power global ambitions, military capability, political and economic influence made the Horn of Africa a pivotal role of geopolitics in shaping the security and economic trajectory. In this context, Security developments in the Horn are being integrated into geopolitical and geo-economics agendas that stretch far beyond the immediate region. On the other hand, the uptick engagement by external actors, and their attendant interests, alliances and agendas offers opportunities for development and integration, but it also poses considerable risks since horn of Africa region are vulnerable to intra- and interstate conflict. Further it raises the prospect of proxy struggles and growing geopolitical interest and tensions which is an obstacle to conflict resolutions lasting peace in the region. Thus the articles argue Rather than seeking to undermine one another, the regimes of the Horn have increasingly tended to support one another. In addition this paper recommends regional institutions such as IGAD need to reconsider dynamics within the Red Sea in line with the aim of building confidence among actors in order to advance common economic and security interests, as well as to ensure the future development of the shared interest.